GENDER REPRESENTATION IN TEXTBOOK BAHASA INGGRIS GRADE X - Cynantia Rachmijati; Sri Supiah Cahyati (STKIP Siliwangi, 2018)
According to ACDP Indonesia, many gender bias contents found in textbooks Bahasa Inggris in Indonesia settings. This study aims at examining the representation of gender on “BahasaInggriskelas X” by Kemendiknas. The criteria of a good textbook should show the relationship of women and men in society based on their role, status, environment, culture and community structures which are displayed in the form of illustrations and descriptions of the sentence. Findings from the book regarding Text: 4,11% visual characters, 28,77% characters mentioned, 57,54% social activities, and 9,58% domestic activity. While findings regarding Visual: 88,89% social activities and 11,11% regarding domestic. Furthermore, the Frequency of occurrence: for male 51,89%. and female 48,11% .Not too many domestic roles and settings found in the book probably because the book is created to inline with Curriculum 2013 where the main purpose of Curriculum 2013 is to develop social skills. It can be concluded that gender representation in this book is dominated by male.